Corrosion‐Resistant Parallel Fixed‐Bed Reactors for High‐Throughput Screening of New Deacon Reaction Catalysts. Issue 7 (July 2014) - Valtchev, Martin; Hammes, Markus; Richter, Rudolf; Höltzen, Heike; Stöwe, Klaus; Maier, Wilhelm F.
Abstract Two ten‐channel fixed‐bed reactor systems were developed for high‐throughput screening of new Deacon catalysts. The sequential ten‐channel reactor allows the determination of the activity of up to ten catalysts per day. With a ten‐channel ageing reactor the long‐time stability of catalytic activity can be tested in parallel. Both systems are robust, quite resistant against corrosion, and use the identical reaction tubes which enable the direct transfer of a catalyst from one to the other system. A mass‐spectrometric pulse method has been developed and applied successfully for the analysis of the corrosive product gas mixture of the Deacon reaction.